Relationship Between Husband’s Support and Exclussive Breast Feeding Execution for Infants at Age of 0 to 6 Months in Sukorejo Village-Tegalrejo Subdistrict-Magelang District Year 2011 - Mundarti Mundarti; Sri Widatiningsih; J. Pratikto (Jurnal LINK, 2012)
Almost 90% of child mortality occured in developing country, over 40% of it was caused by diarhhea and acute respiratory tract infection, which can be prevented by exclussive breasfeeding. Data from the profile of districts/cities in Central Java Province year 2005 showed the average of infants at age of 0 to 6 month who were given exclussive brestfeeding was counted 27.49%. Previous pilot study conducted in Sukorejo Village, Tegalrejo Subdistrict, Magelang District in January 2011 revealed that of 5 breastfeeding mothers who exclussively breasfed their infants, there were 4 mothers who had husband’s support while only 1 mother who had not. This study was intended to identify relationship between husbands’s support and execution of exclussive breastfeeding in Sukorejo Village, Tegalrejo Subdistrict, Magelang District. Analitic survey method was applied in the study with cross sectional approach. Population of the study were breastfeeding mothers having infant of 7 to 12 months old. Total sampling technique was used leading in the amount of 35 respondents. Univariate and bivariate analysis were conducted, and chi square test was applied. The study result showed that table value of x2 =3.841 and count value of x2= 8,733 where it meant that x2 count value x2 table value. The result revealed there was a significant relationship between husbands’s support and execution of exclussive breastfeeding. It can be said in summary that there was a relationship between husbands’s support and execution of exclussive breastfeeding. Therefore it was suggested for health care providers specifically midwives to raise up support and counselling regarding exclussive breasfeeding in order to reinforce the execution of exclussive brestfeeding.